Organisational justice and employee work engagement: LMX as mediator - Hassan, Arif; Al Jubari, Ibrahim Hizam Ali (Inderscience, 2010)
The paper examines the role that organisational justice plays in determining employees' work engagement and the way quality of leader-subordinate relationship (LMX) mediates this association. Data was obtained from an airline company from the Middle East. The sample consisted of 218 employees from several job levels who responded to a questionnaire measuring the study variables. Results indicated that distributive and procedural justice perception promoted quality relationship between leader and subordinate and higher quality of leader-subordinate relationship contributed to employees' work engagement. Among the three organisational justice factors, only interactional justice was related to employee work engagement. The study found a full mediation effect of LMX on interactional justice and employee work engagement.